KAJIAN PROSES RANTAI PASOK PENYEDIAAN RUMAH SUSUN YANG TERJANGKAU OLEH PENGEMBANG BUMN DAN SWASTA DI DKI JAKARTA (STUDI KASUS: SAMESTA SENTRALAND CENGKARENG DAN GREEN PRAMUKA CITY) - Heng, Jeckhi; Tresani, Nurahma; Mahmud, Nasiruddin (Universitas Tarumanagara, 2021)
The provision of affordable housing is still a big issue in every major city in Indonesia. The increasing number of urbanizations hasn’t made the provision of housing in the city of Jakarta also increase. Residents who take part in the urbanization program were from the Middle Class and Low-Income Communities Class. The provision of land for Affordable Flats was still a bit. Based on the presentation of the Director of Housing Financing Planning at the Directorate General of Housing Financing, classic problems have happened since 1992 by the PUPR Settlement Area Development were still related to the housing supply chain process. This research will re-examine the supply chain process that has been carried out by developers and stakeholders in DKI Jakarta as well as solutions to the efforts that will be made to overcome obstacles in the provision of Affordable Flats. The research locations are in Samesta Sentraland Cengkareng and Green Pramuka City. The approach used in this research is a qualitative approach. The analytical method for researching is chronological analysis and comparison of each Affordable Flats where developed by the developer. The results of the study show that the provision of affordable flats is still very influential on the regulations that have been carried out by the government on the land, and the selection of materials for the establishment of Affordable Flats is still very influential. In the case of Samesta Sentraland Cengkareng, the existing regulations at the project site must provide 20% of their development for MBR, and the selection of materials is based on discussions with the construction manager. Even though the license in the Green Pramuka City case was rusunami, there was only anami due to the request of the prospective buyer to use good material specifications. Keywords: flats, affordability; supply chain; low-income communities; developers; stakeholders; government AbstrakPenyediaan hunian yang terjangkau masih menjadi isu besar pada setiap kota-kota besar di Indonesia. Angka urbanisasi yang semakin bertambah tidak membuat penyediaan hunian di kota Jakarta juga ikut bertambah. Penduduk yang ikut program urbanisasi dari Masyarakat Kelas Menengah dan Kelas Masyarakat Berpenghasilan Rendah atau MBR. Penyediaan tanah untuk Rumah Susun yang Terjangkau masih sedikit. Berdasarkan presentasi Direktur Perencanaan Pembiayaan Perumahan Direktorat Jenderal Pembiayaan Perumahan, permasalahan klasik sejak tahun 1992 oleh Pengembangan Kawasan Permukiman PUPR masih berkaitan dengan proses rantai pasok hunian. Pada penelitian ini akan meneliti kembali proses rantai pasok yang sudah dijalankan oleh pengembang-pengembang dan stakeholders yang ada di DKI Jakarta maupun solusi upaya yang akan dilakukan untuk mengatasi hambatan pada penyediaan Rumah Susun yang Terjangkau. Lokasi penelitian berada di Samesta Sentraland Cengkareng dan Green Pramuka City. Pendekatan yang digunakan pada penelitian ini adalah pendekatan kualitatif. Metode analisis yang dilakukan adalah analisis kronologi dan perbandingan pada masing-masing rumah susun yang dikembangkan oleh pengembang. Hasil penelitian menunjukan bahwa penyediaan rumah susun yang terjangkau masih sangat berpengaruh terhadap peraturan yang telah dilakukan oleh pemerintah pada lahan tersebut, serta pemilihan material pada berdirinya rumah susun yang terjangkau masih sangat berpengaruh. Pada kasus Samesta Sentraland Cengkareng, peraturan yang ada pada lokasi proyek mesti menyediakan 20% dari pengembangan mereka untuk MBR, dan pemilihan material berdasarkan hasil diskusi dengan manager konstruksi. Walaupun perizinan pada kasus Green Pramuka City merupakan rusunami, yang ada hanya anami akibat permintaan calon pembeli untuk menggunakan spesifikasi bahan yang baik.